Metajournalistic Discourse on the Commercialization of News: Resistance toward Journalistic Autonomy - Krisdinanto, Nanang (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
The digital evolution in the journalistic arena forces journalists to adapt their practices to the rules that come from the economic arena associated with commercialization. Reduced advertising revenue has resulted in the media tending to prioritize financial survival over journalistic principles or ethics. This research aims to describe how journalists struggle to define journalistic practices amidst the pressure of commercialization, using Bourdieu's theoretical perspective. The method used is metajournalistic discourse, using metajournalistic documents in the form of scripts written by digital journalists who broadcast on Remotivi. Metajournalistic discourse is a textual analysis method that focuses on how journalists tell stories about their journalistic practices, and these stories are assumed to shape the journalistic arena they inhabit. The findings show that journalists experience a paradox in defining and carrying out journalistic practices that are considered ideal. On the one hand, journalists appear to carry out journalistic practices in a situation with a high degree of heteronomy. On the other hand, journalists also seek to develop resistance by maintaining or developing definitions of journalistic practices or norms that are close to the autonomy pole, for example, by defining their journalistic practice with the term